SISTEM KESEHATAN DAN KESELAMATAN KERJA (K3) PADA PERUSAHAAN - Muhammad Shadiqul Mushaddiq; Hasan, Hamzah; RizaL, M. Chaerul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to describe the occupational Health and Safety (K3) system at PT Huady Nickel Alloy in Bantaeng Regency. The problem in this research is the large number of work accident cases. The approach used is a normative star's approach and an empirical juridical approach. The data collection method was carried out by means of interviews. The results of this research show that: the K3 system in this company implements Job Safety Analysis (JSA), where Job Safety Analysis (JSA) for each person or worker about what is done to do the job well and safely, apart from that, guidance is also given before starting a job, safety observations and as a topic at a safety meeting and then as a form of determining the standards needed for safety at work but in the implementation there are still individuals who underestimate the use of PPE and have the potential to cause harm to themselves. PT Huady Nickel Alloy has provided various Apart from providing PPE, these types of facilities also provide treatment such as providing first aid and providing clinics for further examinations.